Music engagement is negatively correlated with depressive symptoms during the COVID‐19 pandemic via reward‐related mechanisms. Issue 1 (19th November 2022) - Mas‐Herrero, Ernest; Singer, Neomi; Ferreri, Laura; McPhee, Michael; Zatorre, Robert J.; Ripollés, Pablo
Abstract: The COVID‐19 pandemic has deeply affected the mental health of millions of people. We assessed which of many leisure activities correlated with positive mental health outputs, with particular attention to music, which has been reported to be important for coping with the psychological burden of the pandemic. Questionnaire data from about 1000 individuals primarily from Italy, Spain, and the United States during May–June 2020 show that people picked music activities (listening to, playing, singing, etc.) most often as the leisure experiences that helped them the most to cope with psychological distress related with the pandemic. During the pandemic, hours of engagement in music and food‐related activities were associated with lower depressive symptoms. The negative correlation between music and depression was mediated by individual differences in sensitivity to reward, whereas the correlation between food‐related activities and improved mental health outputs was explained by differences in emotion suppression strategies. Our results, while correlational, suggest that engaging in music activities could be related to improved well‐being with the underlying mechanism being related to reward, consistent with neuroscience findings. Our data have practical significance in pointing to effective strategies to cope with mental health issues beyond those related to the COVID‐19 pandemic. Abstract : The COVID‐19 pandemic has deeply affected the mental health of millions of people. We assessed which leisure activities correlated with positive mental health outputs, with particular attention to music, which has been reported to be important for coping with the psychological burden of the pandemic. We show that people picked music activities most often as the leisure experiences that helped them the most to cope with psychological distress related with the pandemic. We further demonstrate that greater engagement with music during the pandemic is linked to lower levels of depression.